Single-cell RNA-sequencing identifies various proportions of excitatory and inhibitory neurons in cultured human fetal brain cortical tissues - Liu, Rong; Dong, Wei; Xiong, Dan; Hu, Lanqi; Zhang, Haoran; Yuan, Xiaoping; Tang, Zhonghui; Fu, Fang; Yang, Xin; Wu, Xia (Frontiers in Neuroscience, 2023)
Cortical neural progenitor cells have the potential to differentiate into both excitatory and inhibitory neurons. However, the exact proportions that such progenitor cells differentiate into remain unclear. In this study, we in vitro cultured human fetal brain prefrontal cortical tissues, collected from varied fetal stages, and applied bulk and single-cell level RNA sequencing techniques to examine the resulting neuronal cell types, cell proportions, and the expression levels of the corresponding cell-type marker genes. Our results showed that almost exclusively excitatory and inhibitory neurons were present in the cultures of fetal prefrontal cortex tissues obtained at gestation weeks eleven and twenty, respectively. This abrupt cell proportion transition was largely determined by the differential neural progenitor lineage specificity in the fetal cortical tissues at different stages of fetal brain development. Additionally, we observed that FGF2, a commonly used reagent in the in-vitro culture of neuronal cells strongly affected the transcriptional profiles of cultured fetal cortical tissues. Collectively, our results provide a new strategy to obtain excitatory and inhibitory neuronal cells from the culture of fetal cortical tissues, which could be applied to further study the mechanisms of neurogenesis and neural disease.